Image analysis for classifying coffee bean quality using a multi-feature and machine learning approach - Septiarini, Anindita; Hamdani, Hamdani; Ery Burhandeny, Aji; Nurcahyono, Damar; Eka Priyatna, Surya (IAES International Journal of Artificial Intelligence (IJ-AI), 2024)
Price and customer satisfaction depend on coffee bean quality. The coffee industry must analyze coffee bean quality. Global demand for robusta coffee is high. Coffee industry professionals mostly understand coffee bean quality. Thus, an image analysis using a computer vision-based approach for classifying robusta coffee bean quality is required. Image acquisition, region of interest (ROI) detection, pre-processing, segmentation, feature extraction, feature selection, and classification are covered in this study. A multi-feature derived based on color, shape, and texture features was employed in feature extraction, followed by feature selection using principal component analysis (PCA). Several machine-learning methods classified the coffee beans. The method performance was assessed using precision, recall, and accuracy. The selected features using the backpropagation neural network (BPNN) classifier outperformed others with 98.54% accuracy.